Anti-inflammatory Chitosan/Poly-γ-glutamic acid nanoparticles control inflammation while remodeling extracellular matrix in degenerated intervertebral disc. (15th September 2016) - Teixeira, Graciosa Q.; Leite Pereira, Catarina; Castro, Flávia; Ferreira, Joana R.; Gomez-Lazaro, Maria; Aguiar, Paulo; Barbosa, Mário A.; Neidlinger-Wilke, Cornelia; Goncalves, Raquel M.
Graphical abstract: Abstract: Intervertebral disc (IVD) degeneration is one of the most common causes of low back pain (LBP), the leading disorder in terms of years lived with disability. Inflammation can play a role in LPB, while impairs IVD regeneration. In spite of this, different inflammatory targets have been purposed in the context of IVD regeneration. Anti-inflammatory nanoparticles (NPs) of Chitosan and Poly-(γ-glutamic acid) with a non-steroidal anti-inflammatory drug, diclofenac (Df), were previously shown to counteract a pro-inflammatory response of human macrophages. Here, the effect of intradiscal injection of Df-NPs in degenerated IVD was evaluated. For that, Df-NPs were injected in a bovine IVD organ culture in pro-inflammatory/degenerative conditions, upon stimulation with needle-puncture and interleukin (IL)-1β. Df-NPs were internalized by IVD cells, down-regulating IL-6, IL-8, MMP1 and MMP3, and decreasing PGE2 production, compared with IL-1β-stimulated IVD punches. Interestingly, at the same time, Df-NPs promoted an up-regulation of extracellular matrix (ECM) proteins, namely collagen type II and aggrecan. Allover, this study suggests that IVD treatment with Df-NPs not only reduces inflammation, but also delays and/or decreases ECM degradation, opening perspectives to new intradiscal therapies for IVD degeneration, based on the modulation of inflammation. Statement of Significance: Degeneration of the IVD is an age-related progressive process considered to be the major cause of spine disorders. The pro-inflammatory environment and biomechanics of the degenerated IVD is a challenge for regenerative therapies. The novelty of this work is the intradiscal injection of an anti-inflammatory therapy based on Chitosan (Ch)/Poly-(γ-glutamic acid) (γ-PGA) nanoparticles (NPs) with an anti-inflammatory drug (diclofenac, Df), previously developed by us. This drug delivery system was tested in a pro-inflammatory/degenerative intervertebral disc ex vivo model. The main findings support the success of an anti-inflammatory therapy for degenerated IVD that not only reduces inflammation but also promotes native IVD matrix production.